Measurements of magnetic resonance and high-frequency conductivity at low temperatures and high magnetic fields - Schrama, J; Rzepniewski, E; Ardavan, A; Edwards, R; Klehe, A; Kornilov, A; Singleton, J (1999)
We describe a range of techniques developed by the Oxford group for use in conjunction with the Millimetre-wave Vector Network Analyser in measurements of magnetic resonance and high-frequency conductivity, at extremely low temperatures and high magnetic fields. Included are a variety of resonant cavity techniques. The cylindrical geometry is used to produce high-Q tuneable cavities, ideally suited to measurements of the frequency and temperature dependence of, for example, cyclotron resonance of carriers in GaAs-(Ga,Al)As heterojunctions. A family of rectangular cavities has been designed specifically for measurements of the angle-dependent high-frequency conductivity of organic molecular metals; these systems allow us either to rotate the whole cavity (containing a sample) in the external magnetic field, thus measuring the dependence of a particular component of the conductivity tensor on magnetic field orientation, or to rotate the sample within the cavity, thus measuring different components of the magneto-conductivity. We also describe a non-resonant measurement using a pressure cell with optical access permitting experiments at up to 1.8 GPa. Examples of data obtained from each technique are included.